2013
DOI: 10.1177/1934578x1300800237
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Cytotoxic Evaluation of Essential Oils from Leaves of Porcelia macrocarpa (Annonaceae)

Abstract: This work reports the chemical composition and cytotoxic evaluation of the essential oils from three different samples of the leaves of Porcelia macrocarpa R. E. Fries (Annonaceae). The crude oils, obtained by hydrodistillation procedures, were chemically analyzed by GC/MS. The obtained data indicated the predominance of sesquiterpenes (89.8 ± 0.7%), the main compounds being germacrene D (47 ± 1%) and bicyclogermacrene (37 ± 1%). These oils also contained the monoterpene verbanyl acetate (0.5 ± 0.06%) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
6
20
0
Order By: Relevance
“…[16], the essential oil from the leaves of P. cernuum has promising activity against human and murine tumor cell lines, mainly leukemia and colon carcinoma, higher than the positive control (cisplatin). After chromatographic fractionation, compounds 7 -10 showed strong activity against tested cells with germacrene D (9) and (E)-caryophyllene (10) being the most active in agreement with the literature [8] and explaining the activity of the crude oil from leaves of P. cernuum. A comparison of the IC 50 values of the MeOH extract, essential oil and compounds 7-10 against non-tumorigenic HFF indicated reduced selectivities similar to those determined for tumoral cells.…”
supporting
confidence: 86%
“…[16], the essential oil from the leaves of P. cernuum has promising activity against human and murine tumor cell lines, mainly leukemia and colon carcinoma, higher than the positive control (cisplatin). After chromatographic fractionation, compounds 7 -10 showed strong activity against tested cells with germacrene D (9) and (E)-caryophyllene (10) being the most active in agreement with the literature [8] and explaining the activity of the crude oil from leaves of P. cernuum. A comparison of the IC 50 values of the MeOH extract, essential oil and compounds 7-10 against non-tumorigenic HFF indicated reduced selectivities similar to those determined for tumoral cells.…”
supporting
confidence: 86%
“…Arunkumar et al [7] isolated a steroid positive compound from Z. diphylla that showed promising in vitro and in vivo anticancer activity to Daltonʼs lymphoma ascites cells and was devoid of any toxicity to mice in a short-term toxicity evaluation, indicating that this genus is a source of cytotoxic compounds. The cytotoxic activity of some major constituents present in the leaf essential oil of Z. brasiliensis has been previously assessed, but they showed IC 50 values > 4 µg/mL [13][14][15][16][17][18][19]. Herein, we confirmed that trans-caryophyllene, α-humulene, and trans-nerolidol presented only weak anticancer potential.…”
supporting
confidence: 89%
“…The germacrane group was also highlighted in the study of the essential oil of Porcelia macrocarpa , another Annonaceae species. A mixture of germacrene D and bicyclogermacrene isolated from its oil showed significant cytotoxic potential against HL-60 cells (human leukemia) [ 40 ]. As mentioned before, the oil of Eugenia caryophyllata (clove) exhibits strong cytotoxic activity in HL-60 cells [ 20 ], as well as being active against colon and melanoma cancer cells [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%